The painter [large type] : a novel - Heller, Peter, 1959- (Center Point Large Print, 2014)
"Peter Heller, the celebrated author of the breakout best seller The Dog Stars, returns with an achingly beautiful, wildly suspenseful second novel about an artist trying to outrun his past"--